2014
DOI: 10.1007/s12034-014-0612-2
|View full text |Cite
|
Sign up to set email alerts
|

Porous graphitic materials obtained from carbonization of organic xerogels doped with transition metal salts

Abstract: Porous carbons with a well developed graphitic phase were obtained via the pyrolysis of FeCl 3-, NiCl 2-, and CoCl 2-doped organic xerogels. Doping was realized through salt solubilization in a water/methanol solution of resorcinol and furfural. Carbon xerogels with tailored particles, porous morphology and various degrees of graphitization were obtained depending of the water/methanol ratio and the salt content and type in the starting solution of substrates. When obtained via pyrolysis, carbon xerogels retai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 39 publications
0
24
0
1
Order By: Relevance
“…From Figure , it was observed that the XRD pattern of NiO‐Mn 2 O 3 /C matches with the combination of XRD of Mn 2 O 3 , NiO, and graphitic carbon. The diffraction peaks at 2 θ values of 26.84 o and 43.14 o corresponding to (002) and (101) reflection planes, respectively, indicated the formation of graphitic‐type carbon after pyrolysis . The diffraction peaks at 2 θ values of 32.94 o , 38.34 o , 45.21 o , 49.38 o , 55.36 o , and 66.24 o match with the diffraction pattern of standard Mn 2 O 3 , and correspond to (111), (200), (220), (311), (222), and (400) crystal planes of face‐centered‐cubic (fcc) Mn 2 O 3 , respectively .…”
Section: Resultsmentioning
confidence: 73%
“…From Figure , it was observed that the XRD pattern of NiO‐Mn 2 O 3 /C matches with the combination of XRD of Mn 2 O 3 , NiO, and graphitic carbon. The diffraction peaks at 2 θ values of 26.84 o and 43.14 o corresponding to (002) and (101) reflection planes, respectively, indicated the formation of graphitic‐type carbon after pyrolysis . The diffraction peaks at 2 θ values of 32.94 o , 38.34 o , 45.21 o , 49.38 o , 55.36 o , and 66.24 o match with the diffraction pattern of standard Mn 2 O 3 , and correspond to (111), (200), (220), (311), (222), and (400) crystal planes of face‐centered‐cubic (fcc) Mn 2 O 3 , respectively .…”
Section: Resultsmentioning
confidence: 73%
“…During pyrolysis metallic particles are produced due to carbothermal reduction of FeCl 3 salts. These particles help in formation of porous nanostructured carbon materials [12]. After removing Fe, the NPC was acid functionalized to introduce active oxygen containing groups on the surface.…”
Section: Discussionmentioning
confidence: 99%
“…However, the oxidation and exfoliating processes introduce defects into the graphene structure disrupting the delocalized sp 2 network, adversely affecting its physical and electrical properties and decreasing its chemical stability. 25,26 By contrast, the 'hard' template approach typically involves chemical vapor deposition (CVD) onto commercially available nickel foams with an average pore size in excess of 50 µm. 17,27,28,12 The template CVD graphene produced typically has much higher electrical conductivity than that of graphene derived from graphite oxide however, yields are much lower than those found in graphene oxide self-assembly routes.…”
Section: Introductionmentioning
confidence: 99%